1990
DOI: 10.1002/1097-0142(19900515)65:10<2185::aid-cncr2820651005>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

The colony stimulating factors discovery, development, and clinical applications

Abstract: HE COLONY STIMULATING FACTORS (CSFs) are four T glycoprotein regulators able to control the proliferation and differentiation of granulocytes, monocyte-macrophages, and certain related hemopoietic cells. This account will describe their discovery and characterization, discuss their actions in vitro and in vivo, the role they may play in the development of myeloid leukemia, and their current use clinically to promote hemopoietic regeneration and enhance resistance to infections in patients with cancer and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(49 citation statements)
references
References 82 publications
0
45
0
4
Order By: Relevance
“…Almost all growth factors display endogenous neuroprotective and neurotrophic effects on mature neurons [1]. One of the few growth factors currently approved for clinical use is the granulocyte colony-stimulating factor (GCSF), routinely prescribed to treat neutropenia (low neutrophil count in the blood) [2]. In addition, GCSF can cross the blood-brain barrier, and recent experimental studies have shown that the administration of GCSF is neuroprotective both for in vitro cultured cortical neurons and in vivo focal cerebral ischemia [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all growth factors display endogenous neuroprotective and neurotrophic effects on mature neurons [1]. One of the few growth factors currently approved for clinical use is the granulocyte colony-stimulating factor (GCSF), routinely prescribed to treat neutropenia (low neutrophil count in the blood) [2]. In addition, GCSF can cross the blood-brain barrier, and recent experimental studies have shown that the administration of GCSF is neuroprotective both for in vitro cultured cortical neurons and in vivo focal cerebral ischemia [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies, such as barrier nursing, intravenous immunoglobulins, hematopoietic growth factors and antimicrobial agents, [1][2][3][4] have been proposed in order to decrease infectious episodes among patients receiving intensive chemotherapy. The use of recombinant hematopoietic growth factors has shortened the duration of granulocytopenia and lessened the risk for infection, 5 but there is conflicting evidence concerning the efficacy of these growth factors in preventing infection-related mortality in stem cell transplanted patients. [6][7][8] In the case of antimicrobial agents, selective gut decontamination has decreased both the incidence of Gram-negative bacterial infections in neutropenic patients and the risk of acute graft-versus-host disease (aGVHD) 3,4 and, in addition, several randomized controlled trials have demonstrated a reduction of infections caused by Gram-negative bacteria by using quinolone prophylaxis in neutropenic patients.…”
mentioning
confidence: 99%
“…Autografting of peripheral blood stem cells or progenitors harvested by leukapheresis before chemotherapy can speed haematopoietic recovery (Henon et al, 1992;Roberts et al, 1992;Henon, 1993). Moreover, expansion of surviving progenitor populations and, thereby, an increased output of mature cells has recently been obtained using haematopoietic growth factors, either alone or in combination with bone marrow or peripheral blood stem cell (PBSC) reinfusion (Metcalf, 1990;Lieschke et al, 1992). Most of these haematopoietic growth factors are produced in the bone by the haematopoietic microenvironment comprised of an admixture of several adherent cell types, including fibroblasts, reticular adventitial cells and macrophages (Dexter, 1989;Eaves et al, 1991).…”
mentioning
confidence: 99%